Broad‐Spectrum Liquid‐ and Gas‐Phase Decontamination of Chemical Warfare Agents by One‐Dimensional Heteropolyniobates. (9th April 2016) - Guo, Weiwei; Lv, Hongjin; Sullivan, Kevin P.; Gordon, Wesley O.; Balboa, Alex; Wagner, George W.; Musaev, Djamaladdin G.; Bacsa, John; Hill, Craig L.
Abstract: A wide range of chemical warfare agents and their simulants are catalytically decontaminated by a new one‐dimensional polymeric polyniobate (P‐PONb), K12 [Ti2 O2 ][GeNb12 O40 ]⋅19 H2 O (KGeNb ) under mild conditions and in the dark. Uniquely, KGeNb facilitates hydrolysis of nerve agents Sarin (GB) and Soman (GD) (and their less reactive simulants, dimethyl methylphosphonate (DMMP)) as well as mustard (HD) in both liquid and gas phases at ambient temperature and in the absence of neutralizing bases or illumination. Three lines of evidence establish thatKGeNb removes DMMP, and thus likely GB/GD, by general base catalysis: a) the k(H2 O)/k(D2 O) solvent isotope effect is 1.4; b) the rate law (hydrolysis at the same pH depends on the amount of P‐PONb present); and c) hydroxide is far less active against the above simulants at the same pH than the P‐PONbs themselves, a critical control experiment.